(untitled) (Research, Society and Development, 2020)
The use of biomass energy is increasingly widespread among industries. There is a growing demand for the purchase of biomass aiming at the generation of thermal and electric energy, as in the case of the sugar and energy sectors, pulp and paper and wood panels. The aim of this article is to analyze a biomass supply chain considering the offer, distance and energy characteristics of biomass. The demand for biofuel is from a panel industry located in the Metropolitan Region of Sorocaba. The final cost was calculated based on price quotes, freights and energy properties of each biomass. The biomasses chosen for analysis were: sawdust, wood chips, briquettes, firewood, standing eucalyptus forest (log) and rice husks. It was found that the largest supply of biomass at the lowest cost is in the distances between 50 km and 250 km. The best materials were wood chips and eucalyptus log. Freight was not a determining factor in the final cost of biomass, even for the longest distances. It was concluded that the chip and the log had advantages for different distances.